Choice by lexicographic semiorders - Paola Manzini; Marco Mariotti (Institute for the Study of Labor (IZA), 2009)
We propose an extension of Tversky's lexicographic semiorder to a model of boundedly rational choice. We explore the connection with sequential rationalisability of choice, and we provide axiomatic characterisations of both models in terms of observable choice data.
urn:nbn:de:101:1-20090323153
Keywords: D0; 330; Lexicographic semiorders; bounded rationality; revealed preference; choice; Offenbarte Präferenzen; Präferenztheorie; Beschränkte Rationalität; Theorie